The effects of an audio clip intervention on public knowledge, attitude and perceptions of folic acid intake in preventing birth defects in Kota Bharu - Geok, Tan Beng (2019)
In Malaysia, brochures and pamphlets have been employed intensively at all levels of public health promotion as media tools to improve childbearing women’s preconception folic acid uptake, and to prevent birth defects. Nonetheless, the incidence of birth defects remains an ongoing challenge. This study’s objectives were to (1) evaluate the effects of an audio clip intervention on public knowledge and attitudes to, and perceptions of, preconception folic acid intake in preventing birth defects; and (2) explore the public’s narratives about their knowledge, attitudes, and perceptions, and the intervention in Kota Bharu, Malaysia. This three-phase mixed methods research, involving an interrupted time series (ITS) study and pre/post-in-depth interviews, was undertaken between October 2015 and June 2016. Phase 1 consisted of pre-intervention interviews (baseline), phase 2 the intervention, and phase 3 post-intervention interviews. A structured Folic Acid Knowledge, Attitudes, and Perceptions Questionnaire (FAKAPQ) was used to assess and compare knowledge, attitudes, and perceptions during the baseline and post-intervention phases, with data collected at six time points. Public participants were recruited for two groups using purposive sampling; an intervention group (n=708 from 2 community markets in Kota Bharu) and a control group (no intervention, n=708 from 1 community market in neighbouring Terengganu). The intervention group was subjected to an audio clip on the role of preconception folic acid intake in preventing birth defects, which was played hourly between 8 am and 2 pm (5 times per day) using the public announcement (PA) system. Pre- and post-intervention interviews were conducted with the same 22 (10 male, 12 female) intervention group participants. Segmented regression analysis was used to assess the intervention’s impact. Thematic analysis (constant comparative) of qualitative data from the in-depth interviews added to the study findings. Post-intervention descriptive analysis revealed an improvement in the knowledge and attitude scores but not in the perceptions score. The ITS analysis, however, showed no significant differences in knowledge, attitude, and perceptions scores. Pre-intervention qualitative data revealed three major themes: “partial information”; “lack of communication”; and “acceptance”. The post-intervention data revealed three themes: “increased knowledge”; “improved attitudes and perceptions”; and “improved presentation”. The findings indicate that the use of audio clips for health education is effective in producing a positive effect on the public’s knowledge of, and attitudes to, preconception folic acid intake in preventing birth defects. However, the lack of any significant difference in knowledge, attitudes, and perceptions in the ITS analysis indicates that it may be necessary to implement more repetitive, longer audio clip broadcasts in public health promotion campaigns.